2018
DOI: 10.1002/oby.22223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Education and Experience on Primary Care Providers' Perspectives of Obesity Treatments during a Pragmatic Trial

Abstract: Objective To examine the impact of a one-year pragmatic obesity trial on primary care providers’ (PCPs) perspectives of treatment. Methods PCPs from four intervention (PCP-I) and five control clinics (PCP-C) completed pre- and post-intervention surveys on weight loss counseling, comfort discussing obesity treatments and perceived effectiveness of interventions; questions were rated on 0–10 Likert scales. Only PCP-I received patient updates and education about obesity ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…In a previous study, we surveyed PCPs in an integrated health care system serving a medically underserved population about obesity treatment. PCPs were less comfortable discussing weight‐loss medications than other obesity treatments and thought that weight‐loss medications were less effective than lifestyle change .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we surveyed PCPs in an integrated health care system serving a medically underserved population about obesity treatment. PCPs were less comfortable discussing weight‐loss medications than other obesity treatments and thought that weight‐loss medications were less effective than lifestyle change .…”
Section: Discussionmentioning
confidence: 99%
“…Another study examining pharmacy claims of more than 80 million patients between 2008 and 2011 showed that despite increasing concern over obesity as a clinical problem, the use of weight‐loss medications over this time period actually declined from 45 to 24/100,000 enrollees . These low rates of weight‐loss medication use may reflect provider or patient concerns over the safety and efficacy of these agents, providers’ lack of experience with this class of medications, Food and Drug Administration (FDA) restrictions on long‐term use of older agents, lack of insurance coverage, or bias that weight is primarily a behavioral problem that should be treated with behavioral measures .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, primary care physicians, endocrinologists, and cardiologists, compared with bariatricians, were often unfamiliar with obesity guidelines, and many had unrealistic expectations for weight loss achieved with antiobesity medications and bariatric surgery . These differences are likely related to a knowledge gap among physicians without obesity medicine training because another trial demonstrated that educating primary care physicians increased their appreciation and use of evidence‐based strategies for weight loss . Because many primary care physicians do not feel that they are of the most qualified profession to help individuals with obesity lose weight , understanding which patients with obesity are best served by being treated by an ABOM‐certified physician is critical, particularly as primary care clinicians become increasingly aware of obesity medicine as a referral option for their patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Iwamoto demonstrated similar findings and also clarified the additional impact of physician training. 31 In his study, Iwamoto found that physicians felt comfortable with treating obesity, but their level of comfort was limited to general treatment knowledge such as the importance of exercise, and most of their advice and counseling focused on general advice that exercise was a solution for weight loss. However, once they were educated on the proper medication use for weight loss, their level of confidence to discuss other options increased.…”
Section: Discussionmentioning
confidence: 99%
“…However, once they were educated on the proper medication use for weight loss, their level of confidence to discuss other options increased. 31 With this increase in confidence, physician’s knowledge and advice for their patients with obesity changed and became more specific to the patients’ needs. 31 The study illustrates that whereas PCPs indicate they are knowledgeable about obesity treatment; their knowledge may be limited to general treatment options and their comfort lie in discussing information within their knowledge base.…”
Section: Discussionmentioning
confidence: 99%